How to cheat in After Effects - Perkins, Chad (Focal Press, 2013)
Get the most from the most widely used application in the postproduction field! Gain the insider tips you need to compose eye-catching, imaginative Adobe After Effects projects quickly and effectively. In How to Cheat in After Effects, Second Edition seasoned AE expert Chad Perkins provides dozens of concise, step-by-step tutorials and lavish 4-color illustrations to get you on the fast track to producing amazing motion graphics and visual effects. Updated for CS6, this new edition has been revised to include:A brand new chapter on the most popular.
Includes index. - Print version record
Keywords: Adobe After effects; Cinematography -- Special effects -- Data processing; Image processing -- Digital techniques; Cinéma; Effets spéciaux; Informatique; Traitement d'images; Techniques numériques; digital imaging; Cinematography; Special effects; Data processing; Image processing; Digital techniques